PENGARUH PENDIDIKAN AGAMA ISLAM TERHADAP SIKAP SOPAN SANTUN SISWA DI SMP NIHAYATUL AMAL RAWAMERTA – KARAWANG - Ayu Fitria (Universitas Nurul Jadid Paiton Probolinggo, East Java, 2020)
This research method is using descriptive quantitative method. The population of this research is the students of Nihayatul Amal Middle School. The sample was taken purposively. The Data collection used interviews, questionnaires and documentation. Data analysis used quantitative descriptive analysis. The results showed: 1). The Reality of Islamic Education at Nihayatul Amal Middle School, Islamic Education which was implemented in Nihayatul Amal Middle School is Moral Education which is implemented in accordance with the existing curriculum at school, 2). The Reality of Manners of Students at Nihayatul Amal Middle School shown that the students loved each other, said with good words, and taught according to the religion rule by the Islamic Sharia. In addition, the students also respect and love teacher so much. 3). The Influenced of Islamic Education based the Attitude of Polite Students in Nihayatul Amal Middle School, Rawamerta Karawang.